Arab Republic of Egypt : Request for a 12-Month Stand-By Arrangement-Press Release; Staff Report; and Statement by the Executive Director for the Arab Republic of Egypt. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2020)
Egypt's hard-won macroeconomic stability achieved during the three-year arrangement under the Extended Fund Facility (EFF) now faces a significant disruption due to the COVID-19 pandemic. Growth is expected to slow in both FY2019/20 and FY2020/21 as tourism has been halted and domestic activity curtailed. The external accounts have come under pressure due to capital outflows and the shock to tourism and remittances. The authorities responded with a broad package to scale up the health system's capacity and policies to support the people and the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet